Mechanobiology of indirect bone fracture healing under conditions of relative stability: a narrative review for the practicing clinician - Benulič, Črt; Canton, Gianluca; Rasio, Nicholas; Murena, Luigi; Kristan, Anže (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Mechanical influence on secondary fracture healing remains an incompletely understood phenomenon. This is of special importance in biological osteosynthesis, where stability is sacrificed for the sake of an optimal biological fracture environment. Under condition of relative stability, a wide range of biomechanical conditions can be achieved. Mechanobiology, which studies mechanical influences on biological systems has become a large, interdisciplinary field. The aim of this article is to present a comprehensive synthesis of the literature for the practicing clinician, with insights relevant to their practice of fracture care.Methods: The MEDLINE online database (Pubmed) was searched in September 2021 for relevant articlesResults: The search provided 816 results, which were scanned by the first author by the title and abstract. With relevance to the research topic, 59 articles were chosen and read in detail. Another 70 articles were added by screening the references of relevant articles. A total of 129 articles were read and analysedConclusions: Mechanical environment plays a crucial role in the fracture healing process. The definition of an optimal mechanical environment still evades us, due to the complexity of the problem. Computational models could replicate the complex mechanical environment of bone healing in humans but require detailed knowledge of mechano-transduction and material properties of healing tissues. The literature reminds us of the importance of adequate stiffness of constructs used under conditions of relative stability. Hopefully, further research in this field will result in not only empirical but more accurate and evidence-based assessments of osteosynthesis fixations.